Homework is important part of the lesson - Kochkorova Zulfizar Abduxamid qizi; Nilufar, Ismatilloeva (Journal of Innovation in Education and Social Research, 2023)
Homework is an important part of this lesson, various exercises and activities increase the interest of students. In this article, you can get general information about the role and importance of home theater. This article attempts to explore the benefits of this homework and homework assignment problems as well. The article includes several samples. Student-centered assignments that are developmentally appropriate, authentic, and experiential and challenging.